2022
DOI: 10.1002/jee.20450
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork facilitation and conflict resolution training in a HyFlex course during the COVID‐19 pandemic

Abstract: Background We evaluated the effect of three teaching strategies to facilitate teamwork in a systems analysis and design course during the COVID‐19 pandemic: (1) offering a HyFlex version of the course, (2) facilitating scheduled online teamwork sessions for all students, and (3) providing conflict resolution training to help teams overcome collaboration challenges. Purpose/Hypothesis To identify the impact of these instructional strategies and answer four research questions, we measured (1) performance, dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Communication between team members has also been identified as important in influencing the social dimensions of teams [16]. Thus, the implications for facilitating effective team interactions in the context of higher education relate to identifying strategies and pedagogical approaches that promote collaboration and communication processes [57]. Research suggests that teamwork interventions effectively develop, support, and improve teamwork processes [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…Communication between team members has also been identified as important in influencing the social dimensions of teams [16]. Thus, the implications for facilitating effective team interactions in the context of higher education relate to identifying strategies and pedagogical approaches that promote collaboration and communication processes [57]. Research suggests that teamwork interventions effectively develop, support, and improve teamwork processes [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have suggested that the university is an appropriate place to further such skills and have indeed found that they have been incorporated into engineering degree requirements [11,37,38]. Teamwork has been shown to benefit active student engagement, social and interpersonal skills, cooperation, and collaboration [39][40][41].…”
Section: An Overview Of Teamwork In Stem and Its Connection To Soft S...mentioning
confidence: 99%
“…Team conflicts can stem from many sources, including tasks, processes, relationships, and status. Nonetheless, teaching students to use conflict resolution strategies has been shown to mitigate ill-effects [15].…”
Section: Conflict Management and Measuring Team Performancementioning
confidence: 99%